PROVISION OF SOCIALIZATION OF THE PERSONALITY IN THE PRESCHOOL CHILDHOOD IN THE MULTICULTURAL EDUCATIONAL ENVIRONMENT OF TRANSCARPATHIA - Anna Reho (Vasyl Stefanyk Precarpathian National University, 2015)
The rapid tempo of social changes is inherent in the modern Ukrainian society that has resulted in the actual and problematic personality socialization questions in preschool childhood. This period is exactly that sensitive period for the primary child world view formation, consciousness, social features etc. The stay in preschool educational institution plays an important role in preschool age child personality development. Transcarpathian region is the region situated on the southwest of Ukraine within the western part of Ukrainian Carpathians and Transcarpathian lowland. At about 80% of the region's territory is covered by the Carpathian Mountains. In accordance with the Ukrainian Law "On the Status of Mountainous Settlements in Ukraine", until recently 192 settlements (31% out of the total quantity) belong to the mountainous. Volovets and Mizhgirya districts fully subject to the action of the above indicated law, while in other districts the portion of settlements with the mountainous settlements status is presented from 13,6 (in Mukachevo district) up to 84,4 percent (in Rakhiv disctrict). In our publication we will pay attention to four mountainous districts of Transcarpathian region: Velykyi Bereznyi, Volovets, Mizhgirya and Rakhiv districts. This publication presents the comparative status analysis of preschool age children support carried out by the preschool educational institutions in Transcarpathian region in the period starting from the year of 2000 until 2013. In the mountainous districts of Transcarpathian region the preschool educational institutions establishment, quantity of children in them and preschool institutions loading tendency analysis is completed. The distribution of preschool educational institutions as per children educational languages is given in this article.The above mentioned confirms, that in recent years, active attention has been paid to the new preschool institutions creation, namely in mountainous and half mountainous districts of Transcarpathian region. Also, the rising tendency of the number of children in these institutions is observed. However, the need to expand the children coverage by preschool education is constantly felt. Allocation of children in permanent preschool institutions in accordance to their language of education has been changed significantly; nevertheless it still does not satisfy the national minorities' needs, due to the fact that it does not correspond to the quantitative composition of modern Transcarpathian population.